2022
DOI: 10.3390/agronomy12030657
|View full text |Cite
|
Sign up to set email alerts
|

Differing Roles of Bacterial and Fungal Communities in Cotton Fields by Growth Stage

Abstract: The global demand for cotton makes sustainable cotton production an important issue that can be improved by a better understanding of the influence of soil microbes on cotton growth. We collected cotton field soils at the seedling and flowering/boll-setting (FBS) stages in order to obtain soil properties and cotton growth indices. Bacterial and fungal community compositions were assessed by high-throughput sequencing of 16S rRNA and internal transcribed spacer genes, respectively, after which the differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 64 publications
1
2
0
Order By: Relevance
“…The composition of the microbial community in the third and fourth years is close, while that in the second year is between the first year and the last two years ( Figure 3 ). NMDS shows the process of continuous and gradual change in the microbial community under the effect of plants, which is consistent with the previous research on rice (Zhang J. et al, 2018 ) and cotton (Li D. et al, 2022 ). Studies have shown that rotation can improve microbial diversity, but the mechanisms are not fully elaborated (Venter et al, 2016 ; Xie et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…The composition of the microbial community in the third and fourth years is close, while that in the second year is between the first year and the last two years ( Figure 3 ). NMDS shows the process of continuous and gradual change in the microbial community under the effect of plants, which is consistent with the previous research on rice (Zhang J. et al, 2018 ) and cotton (Li D. et al, 2022 ). Studies have shown that rotation can improve microbial diversity, but the mechanisms are not fully elaborated (Venter et al, 2016 ; Xie et al, 2022 ).…”
Section: Discussionsupporting
confidence: 91%
“…35 Notably, recent research by Li et al highlighted that microbial richness and biomass exhibit significant disparities between the seedling period and subsequent flowering and boll periods. 36 Furthermore, the stability of the soil bacterial community decreases as cotton plants progress through their life cycle, particularly during the flowering and boll periods. Interestingly, alterations in the bacterial community composition are associated closely with changes in the growth indices of cotton during the seedling and flowering periods although no similar correlations were observed with fungal community composition.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, recent research by Li et al . highlighted that microbial richness and biomass exhibit significant disparities between the seedling period and subsequent flowering and boll periods 36 . Furthermore, the stability of the soil bacterial community decreases as cotton plants progress through their life cycle, particularly during the flowering and boll periods.…”
Section: Introductionmentioning
confidence: 99%